Trace metals on anaerobic reactors treating domestic sewage - Silva, Julliana Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The use of anaerobic bioreactors for wastewater treatment depends on the adequate set-up and control of the physical, chemical, and biological parameters. In order to keep stable and suitable performance, it is essential to know the characteristics of the wastewater to be treated to choose the best treatment and reactor configuration, find the optimal hydraulic retention time (HRT), operational conditions and nutrients requirement. Regarding nutrients, deficiencies or excess of macro or micronutrients in anaerobic wastewater treatment systems are not a rare phenomenon. Knowing the wastewater composition and the biomass trace metals requirement in the system are necessary to achieve a maximal substrate conversion. Hence, providing a rational trace metal supplementation to the reactor. Therefore, in this thesis, the trace metal profile of domestic sewage (DS) treated in an innovative configuration of anaerobic reactor, the anaerobic structured-fixed bed reactor (ASTBR) is studied, together with the boundary conditions for stable operation, according to the organic matter load and trace metals contribution. In addition, a UASB reactor is operated in parallel as a model reactor to compare the ATBSR performance and as a source of sludge for the optimization of trace metals in DS anaerobic digestion, improving methane production. The results are presented in three individual papers, two published in international journals.

O uso de biorreatores anaeróbicos para tratamento de águas residuais depende da configuração e controle adequados dos parâmetros físicos, químicos e biológicos. Para manter um desempenho estável e adequado, é essencial conhecer as características das águas residuais a serem tratadas para escolher o melhor tratamento e configuração do reator, encontrar o tempo de retenção hidráulica (HRT) ideal, condições operacionais e requisitos de nutrientes. Em relação aos nutrientes, deficiências ou excesso de macro ou micronutrientes em sistemas de tratamento de águas residuais anaeróbicos não são um fenômeno raro. Conhecer a composição das águas residuais e os requisitos de metais traço da biomassa no sistema são necessários para atingir uma conversão máxima do substrato. Portanto, fornecendo uma suplementação racional de metais traço ao reator. Portanto, nesta tese, o perfil de metais traço do esgoto doméstico (DS) tratado em uma configuração inovadora de reator anaeróbico, o reator anaeróbico de leito fixo estruturado (ASTBR) é estudado, juntamente com as condições de contorno para operação estável, de acordo com a carga de matéria orgânica e contribuição de metais traço. Além disso, um reator UASB é operado em paralelo como um reator modelo para comparar o desempenho do ATBSR e como uma fonte de lodo para a otimização de metais traço na digestão anaeróbica de DS, melhorando a produção de metano. Os resultados são apresentados em três artigos individuais, dois publicados em periódicos internacionais.
Metais traço em reatores anaeróbios: tratando esgoto doméstico
Keywords: Anaerobic treatment; Anaerobic reactors; Trace metals; UASB reactor; Anaerobic fixed-structured bed reactor; Methane production; ASTBR; Placket burman; Metais traço; Reatores anaeróbios; Esgoto doméstico